2013
DOI: 10.4293/108680813x13654754534477
|View full text |Cite|
|
Sign up to set email alerts
|

Cost Effective Laparoendoscopic Single-Site Surgery with a Reusable Platform

Abstract: The authors found that laparoendoscopic single-site surgery with a reusable platform was feasible for various urologic entities, yielding favorable cosmetic and functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…To date, there have been no cost-effectiveness analyses performed on the implementation of LESS or hybrid LESS in urology departments that take into account the surgical time and the costs resulting from hospitalization. However, the reusable nature of the instruments and reduced hospital stays resulting from a faster recovery with lower analgesic needs suggest significant advantages for the LESS approach with reusable materials [20,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no cost-effectiveness analyses performed on the implementation of LESS or hybrid LESS in urology departments that take into account the surgical time and the costs resulting from hospitalization. However, the reusable nature of the instruments and reduced hospital stays resulting from a faster recovery with lower analgesic needs suggest significant advantages for the LESS approach with reusable materials [20,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…In our present work, no postoperative complications occurred within 6 months after LESSPL. In a series of 15 consecutive LESSPL in males with localized high risk prostate cancer, Schwentner et al reported on one patient with inadvertent bowel injury, requiring intracorporal suturing [ 11 ]. In our view, patient safety should be a major issue in a pure diagnostic staging procedure, especially when a novel minimally invasive technique is used.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier publication, we estimated cumulative cost of 10 LESS procedures, performed with different single ports, and identified the reusable X-Cone as being the most cost-effective [ 10 ]. In their recent publication on different urologic LESS procedures, Schwentner et al found that LESS nephrectomy performed with the X-Cone is more cost-effective than conventional multiport laparoscopic nephrectomy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we selected some of the most commonly used devices: the SILS Port (Covidien, Mansfield) [3,7,8], which requires a 2-cm minimum incision, but because of its foam like structure perfectly adapts to the abdominal wall thus preventing gas leakage; the GelPOINT Advanced Access Platform (Applied Medical, CA) as a disposable alternative to the first, a device that has gradually grown in importance, especially in general surgery procedures [5,9]; and, as a reusable alternative, we opted for the XCONE (Karl Storz GmbH & Co, Tuttlingen, Germany) [1,10,11].…”
Section: Introductionmentioning
confidence: 99%